2016
DOI: 10.1155/2016/4691275
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the Pipeline Embolization Device in Posterior Communicating Artery Aneurysms Associated with a Fetal Posterior Cerebral Artery

Abstract: The pipeline embolization device has emerged as an important endovascular option. This is in part due to safety, efficacy, and possibly the ability to shorten the operative time considerably. With this new technology, some limitations are emerging as experience accumulates. We report three cases of posterior communicating (PCOM) artery aneurysms associated with fetal posterior cerebral artery where pipeline embolization was unsuccessful in obliterating the aneurysms. PCOM artery aneurysms associated with a fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
0
22
1
1
Order By: Relevance
“…The only predictive factor for aneurysm obliteration after treatment was the presence of an artery arising from neck of the aneurysm, which dramatically reduces the rate of complete aneurysmal obliteration. This is in contrast with previous studies 13,15 which showed a fetal PCA as the only predictor of failed aneurysm occlusion. Our study demonstrates that one PED is sufficient to induce occlusion or near-occlusion of most aneurysms, especially those without a branching artery from the aneurysm neck.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The only predictive factor for aneurysm obliteration after treatment was the presence of an artery arising from neck of the aneurysm, which dramatically reduces the rate of complete aneurysmal obliteration. This is in contrast with previous studies 13,15 which showed a fetal PCA as the only predictor of failed aneurysm occlusion. Our study demonstrates that one PED is sufficient to induce occlusion or near-occlusion of most aneurysms, especially those without a branching artery from the aneurysm neck.…”
Section: Discussioncontrasting
confidence: 99%
“…They described failed obliteration of these aneurysms due to the high flow and demand through the fetal PCA. 15 In contrast to Saatchi et al, the goal of the treatment in their series was obliteration of the aneurysm, and these aneurysms subsequently underwent surgical clipping. 21 Tsang et al reported similar obliteration rates for PCOM aneurysms with fetal PCA.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We read with interest the article by Zanaty et al “Failure of the Pipeline Embolization Device in Posterior Communicating Artery Aneurysms Associated with a Fetal Posterior Cerebral Artery” [1]. …”
mentioning
confidence: 99%